Socio-environmental conflicts : environmental law as an instrument for legitimizing the actions of public authorities an intervention in Jardim Icaraí, Curitiba, PR - Rosirene Martins Lima; Joaquim Shiraishi Neto (Ambiente & Sociedade, 2015)
The objective of this project is to focus on the environmental conflict involving the government and the residents of Jardim Icaraí in Curitiba, Brazil. This exercise examines environmental law as an instrument for producing and disseminating the "official version" of the environment and the city's intervention plan. Environmental Law not only provides legitimacy to this plan, but is also intimately associated to the urban policies in Curitiba.